A Gardener's Vision: UAVs and the Dehumanisation of Violence. Issue 6 (2nd November 2018) - Renic, Neil C.
Abstract : UAVs undermine the shared recognition of humanity between enemies that has historically functioned as a prerequisite for battlefield restraint.